Feasibility and Robustness of 3T Magnetic Resonance Angiography Using Modified Dixon Fat Suppression in Patients With Known or Suspected Peripheral Artery Disease - Weiss, Karl Jakob; Eggers, Holger; Stehning, Christian; Kouwenhoven, Marc; Nassar, Mithal; Pieske, Burkert; Stawowy, Philipp; Schnackenburg, Bernhard; Kelle, Sebastian (Frontiers in Cardiovascular Medicine, 2020)
Contrast enhanced magnetic resonance angiography (CE-MRA) is a well-established noninvasive imaging technique for the assessment of peripheral artery disease (PAD). A subtractionless method using modified Dixon (mDixon) fat suppression showed superior image quality at 1.5T over the common subtraction method, using a three- positions stepping table approach with a single dose of contrast agent. The aim of this study was to investigate the feasibility of subtractionless first-pass peripheral MRA at 3T in patients with known or suspected PAD and to compare the performance in terms of vessel-to-background contrast (VBC), signal-to-noise ratio (SNR) and subjective image quality to conventional subtraction MRA. Ten patients (mean age 69 years ± 12 standard deviation (SD)) with known or suspected PAD were examined on a clinical 3T scanner (Ingenia, Philips Healthcare, Best, Netherlands) at three table positions using subtractionless and subtraction first-pass peripheral MRA. Two readers rated image quality on a four- point scale. Interobserver agreement was expressed in quadratic weighted κ values. Vessel-to-background contrast was assessed with a semi-automated process and signal-to-noise ratio was compared in a healthy volunteer. Subjective image quality was significantly better with the subtractionless method overall (mean image quality for mDixon imaging: 2.88±0,32 SD vs. for subtraction imaging: 2.57±0,48 SD; P < 0.001) and per table position ( abdominal position: 2.88±0.32 SD vs. 2.57±0.48 SD; P < 0.001); upper leg position: (2.97±0.15 SD vs. 2.68±0.37 SD; P < 0.001; lower leg position: 2.60±0.50 SD vs. 2.13±0.60 SD; P < 0.001). Vessel-to-background contrast increased by 22% with the subtractionless method overall (mean VBC for mDixon imaging: 23.16±8.4 SD vs. for subtraction imaging: 19.00±8.1 SD; factor 1.22, P < 0.001). SNR was 82 % higher with the subtractionless method (overall SNR gain 1.82; P < 0.001). This study demonstrated the feasibility and robustness of subtractionless first-pass peripheral MRA at 3T in patients with known or suspected PAD using a three- positions stepping table approach with a single dose of contrast agent. It showed increased image quality compared to the conventional subtraction method and superior performance in terms of SNR and vessel-to-background contrast.